LIVE FORENSIK UNTUK ANALISA ANTI FORENSIK PADA WEB BROWSER STUDI KASUS BROWZAR - Tri Rochmadi (Indonesian Journal of Business Intelligence (IJUBI), 2019)
Cybercrime continues to increase and innovate along with the rapid development of internet and more easily accessible everywhere. Most business organizations have used the internet for its operations so that the use of browsers is a necessity to support work. So that the browser also adjusts to improve security on the user's side so that information accessed by users cannot be known by other users. Browzar is a browser that answers these challenges, where Browzar can run without having to be installed on the computer and automatically deletes information generated by the use of the browser itself. However, these advantages become a challenge for investigators because these advantages can be exploited by cybercriminals to eliminate, minimize existing digital evidence. This study intends to analyze and find digital evidence in criminal cases using Browzar with Live Forensic. Digital evidence is obtained using dumpit for data acquisition and forensic volatility memory and winhex to analyze data and information on RAM. Results of the study were able to obtain information that could be used for digital evidence on Browzar web browser, namely URL history, account used log in, namely username and password, timestamp, that is, the user access time to a web page.